Interleukin-15 deficient rats have reduced osteopontin at the maternal-fetal interface - Baines, Kelly J.; Klausner, Michelle S.; Patterson, Violet S.; Renaud, Stephen J. (Frontiers in Cell and Developmental Biology, 2023)
Uterine Natural Killer (NK) cells are the predominant immune cells within the decidua during early pregnancy. These cells are thought to regulate aspects of decidualization and placental development, but their functions remain poorly characterized, especially in species with deeply invading trophoblasts such as humans and rats. Interleukin-15 (IL-15) is a cytokine required for NK cell development and survival. IL-15 mutant (IL15Δ/Δ) rats lack NK cells and exhibit altered placental development with precocious trophoblast invasion. In this study, we profiled gene expression differences between wild-type and IL15Δ/Δ implantation sites to reveal candidate factors produced by uterine NK cells that may regulate placentation and trophoblast invasion. There were 257 genes differentially expressed between wild-type and IL15Δ/Δ implantation sites on gestational day 9.5, including decreased expression of various NK cell markers in IL15Δ/Δ rats, as well as Spp1, which encodes osteopontin (OPN). In wild-type rats, OPN was present within the decidua basalis and adjacent to the primitive placenta, and OPN colocalized with the NK cell marker perforin. OPN was also detectable in uterine glands. Conversely, in IL15Δ/Δ rats, OPN and perforin were not readily detectable in the decidua despite robust OPN levels in uterine glands. Neutralization of OPN in media conditioned by cells isolated from the decidua decreased invasion of rat trophoblasts, suggesting that reduced levels of OPN are unlikely to account for the precocious trophoblast invasion in IL15Δ/Δ rats. Nonetheless, our study suggests that osteopontin is expressed by NK cells at the maternal-fetal interface in rats and may contribute to modulation of trophoblast invasion.